Media Pembelajaran PJOK pada Masa Pandemi Covid-19 di SMP Se-Kecamatan Gondang Kabupaten Sragen Tahun Ajaran 2020/2021 - Heru Trianto Putro; Sulaiman Sulaiman (Universitas Negeri Semarang, 2022)
This study aims to analyze online learning media for PJOK subjects during the Covid-19 pandemic. The method used in this study is qualitative with a descriptive approach. Data were collected by observing, interviewing, and documenting the online learning process for PJOK subjects at 4 junior high schools in Gondang District, then the data was analyzed based on an interactive model with five interacting components, namely: data collection, data reduction, data presentation, conclusion drawing, and verification. The results of this study found that the online learning process for PJOK subjects at 4 junior high schools in Gondang District used media for delivering materials and assignments in the form of Google Classroom, Whatsapp, and Google Forms, with media for delivering materials using PDF, PPT, and video documents. . For media assessment, teachers use two kinds of assessment, namely cognitive and psychomotor. Cognitive assessment is obtained from the results of tests and assignments in the form of knowledge questions which are converted to Google Spreadsheets. While the psychomotor assessment was obtained from the assignment to make practical videos. The conclusions from this study were that the overall online learning process for PJOK subjects went well and teachers and students were able to adapt in the midst of a pandemic to carry out learning properly.